Thiamine as a metabolic resuscitator in septic shock: a meta-analysis of randomized controlled trials with trial sequential analysis - Frédéric Sangla; Thomas Verissimo; Anna Faivre; Térence Glauser; Saw Kian Cheah; Benjamin Assouline; Sebastian Sgardello; David Legouis; David Legouis (Frontiers in Medicine, 2023)
ObjectiveSeptic shock is one of the most common reasons for admission to the Intensive Care Unit (ICU) and is associated with high mortality. Fundamentally, its management rests on antibiotics, fluid therapy and vasopressor use while many adjunctive therapies have shown disappointing results. Thiamine has recently gained interest as a metabolic resuscitator, though recent trials have tempered this enthusiasm, more specifically when thiamine is associated with ascorbic acid. However, thiamine use alone has been poorly investigated.DesignWe conducted a systematic review and meta-analysis of randomized controlled trials (RCTs) in septic shock patients to assess the effects of thiamine without ascorbic acid as an adjunctive therapy.SettingPubMed, Embase and the Cochrane library databases were searched from inception to April of 2023. Data were extracted independently by two authors. The main outcome was mortality.SubjectsWe included RCTs comparing standard care using thiamine alone, to standard care or placebo, in patients admitted to the ICU with sepsis or septic shock.Main resultsWe included 5 RCTs (n = 293 patients). In this analysis, use of thiamine alone did not significantly change mortality, RR 0.87 (95%CI 0.65; 1.16, I2 = 21%) p = 0.34.ConclusionCurrent RCTs did not show an improvement in mortality when using thiamine in septic shock patients as an adjunctive therapy. However, these trials are largely underpowered for a definitive conclusion to be drawn. Further studies are therefore needed to assess the effects of thiamine without ascorbic acid as an adjunctive therapy.